A Look at the economic and financial education in elementary school - Mogollón-Guerrero, Mónica Andrea; Molano-Castro, Marisol Zoraya; Mesa-Jiménez, Fredy Yesid (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article is the result of a documentary review, carried out for the research called "Pedagogical Practices in Financial and EconomicEducation in Elementary School", which is implemented at Institución Educativa Silvestre Arenas de Sogamoso (Boyacá, Colombia) in grades 5A and 2B. After a review of international and national policies on this subject, it is concluded that it is necessary the transversal articulation forthe development and execution of a project in Financial and Economic Education at the level of the Educational Institution.